2013
DOI: 10.1038/kisup.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese approach for CKD-MBD

Abstract: Disturbances in mineral and bone metabolism have a critical role in the pathogenesis of cardiovascular complications in patients with chronic kidney disease (CKD). The term ‘renal osteodystrophy' has recently been replaced by ‘CKD-mineral and bone disorder (CKD-MBD)', which includes abnormalities in bone and mineral metabolism and vascular calcification. The Japanese Society for Dialysis Therapy clinical practice guideline for the management of secondary hyperparathyroidism in chronic dialysis patients was ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…These target ranges for serum phosphorus, calcium, and PTH in the guideline are based on survival data of Japanese dialysis patients. Given that Japanese dialysis patients tend to have a longer dialysis vintage than their American and European counterparts, parathyroid control should be initiated at an early stage of CKD in this patient population ( 7 ). Furthermore, circulating phosphorus and calcium levels contribute to the life prognosis and appear to be more significant to this end than the effects of the parathyroid function ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These target ranges for serum phosphorus, calcium, and PTH in the guideline are based on survival data of Japanese dialysis patients. Given that Japanese dialysis patients tend to have a longer dialysis vintage than their American and European counterparts, parathyroid control should be initiated at an early stage of CKD in this patient population ( 7 ). Furthermore, circulating phosphorus and calcium levels contribute to the life prognosis and appear to be more significant to this end than the effects of the parathyroid function ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The associated CKD-MBD in this patient group is a systemic disorder presenting as abnormalities in the parathyroid hormone (PTH), calcium, phosphorus, and vitamin D metabolism ( 2 , 5 ). Therefore, the CKD-MBD treatment guidelines specifically help achieve target levels of serum phosphorus, followed by calcium and PTH; this order of priority is set by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative™ guidelines ( 6 , 7 ). It is now widely accepted that this dysregulated mineral metabolism in CKD not only results in bone disease but also increases vascular calcification, leading to an increased cardiovascular risk and a reduced survival ( 5 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease–mineral and bone disorder (CKD-MBD) is a growing health care concern associated with secondary hyperparathyroidism, mineral abnormalities, and increased risk of cardiovascular disease [ 16 , 17 ]. As one of the most common abnormalities of CKD-MBD, secondary hyperparathyroidism leads to nodular transformation of the parathyroids in up to 75 % of cases [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, compared to the wide attention in the derangement of calcium/phosphate metabolism and the vascular/valvular calcification, the magnesium metabolism is usually neglected and is still among the less well understood clinical problems encountered by nephrologists until now. 22,23 Recently, since numerous studies suggested an association between hypomagnesaemia and risk factors of cardiovascular disease, such as diabetes mellitus, metabolic syndrome, coronary artery disease and atherosclerosis risk in the general population, 24,25 the impact of magnesium disorders on the prognosis of patients with chronic kidney disease has received a great deal of interest.…”
Section: Discussionmentioning
confidence: 99%